1990
DOI: 10.1071/rd9900089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous infusion of oxytocin on prostaglandin F2 alpha secretion and luteolysis in the cyclic ewe

Abstract: Circulating concentrations of 13,14-dihydro-15-keto PGF2 alpha (DHKF2 alpha), luteinizing hormone (LH) and prolactin (PRL) have been measured in cyclic ewes treated with continuous infusions of oxytocin, in order to investigate the mechanism by which the treatment delays luteal regression. Continuous infusion of oxytocin reduced prostaglandin F2 alpha (PGF2 alpha) secretion but had no detectable direct effect on LH or PRL. Oxytocin (3 nmol h-1 i.v.) given from Day 12 or 13 until Day 18 after oestrus delayed lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…In nonpregnant women (Richardson & Masson, 1985) and sheep (Rodgers et al, 1985), basal as well as gonadotrophin-stimulated pro¬ gesterone secretion from the corpus luteum, in vitro, remained unaffected by oxytocin. Further¬ more, there is evidence that oxytocin infusion has no effect on progesterone secretion in cyclic sheep (Sheldrick & Flint, 1990), cattle (Gilbert et al, 1989) or monkeys (Wilks, 1983). These results are in agreement with our earlier study on oxytocin receptors in sheep (Sernia et ai, 1989).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In nonpregnant women (Richardson & Masson, 1985) and sheep (Rodgers et al, 1985), basal as well as gonadotrophin-stimulated pro¬ gesterone secretion from the corpus luteum, in vitro, remained unaffected by oxytocin. Further¬ more, there is evidence that oxytocin infusion has no effect on progesterone secretion in cyclic sheep (Sheldrick & Flint, 1990), cattle (Gilbert et al, 1989) or monkeys (Wilks, 1983). These results are in agreement with our earlier study on oxytocin receptors in sheep (Sernia et ai, 1989).…”
Section: Discussionsupporting
confidence: 82%
“…The jugular plasma concen¬ tration of oxytocin did not change significantly from a control value of 2-5 + 1-5 pg OT/ml (Fig. 1), while in the oxytocin-infused group the concentration increased from 9-6 + 12 to 202 + 50 pg OT/ ml at 1 h and to 268 ± 80 pg OT/ml at 4 h. A striking, but not unusual (Flint et ai, 1989;Sheldrick & Flint, 1990) groups. In the saline-infused group, no significant changes in concentration were observed over the 4h of infusion, while a significant decrease (anova, < 001) occurred in the oxytocin-infused group.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…These studies suggest that endogenous oxytocin could be of physiological importance in the regulation of the LH surge, but other workers have treated rats with either oxytocin or an oxytocin antiserum and reported no change in LH release (Lumpkin et al, 1983;Sarker, 1988). This relationship has not been investigated in detail in ewes, although Sheldrick & Flint (1990) found that a relatively low dose (3 nmol h~1) oxytocin infusion had no effect on LH secretion during the luteal phase. In their study one ewe that underwent luteolysis during treatment had a normal LH surge.…”
Section: Discussionmentioning
confidence: 95%
“…Continuous infusion of oxytocin into the uterus of cyclic ewes and cows (Gilbert et ai, 1989) prolongs the oestrous cycle, and in the ewe results in decreased oxytocin receptor concentrations and a decrease in PGF-2a concentrations (Sheldrick & Flint, 1987).…”
Section: Introductionmentioning
confidence: 99%